5 - Les initiatives féminines au Sénégal : une réponse à la crise ? - Sow, Fatou (Africa Development, 1993)
The study of the social dynamics of the Senegalese crisis reveals the growing importance of women's initiatives in peasant strategies, the informal sector and business . The crisis led to the opening up of new spaces and possibilities for women which impacted on their status , their role and their participation in production. These changes have brought back the issue of power distribution between sexes within the family and the society. However, the major problem that this study reveals is that development policies have never established a serious continuous and sustainable policy towards women's initiatives. Wofnens participation in development policies remains dominated by insignificant projects in spite of the existence of numerous concrete initiatives, the emergence of a group of entrepreneurs that came from the informal sector which they dominated largely. Women's role as active actors in the economy is recognized and accepted by all. However it is important for the practices and the system to also accept to play the game: institutions, bank credit, absence of sexist discrimination. These are the genuine stakes.